2022
DOI: 10.1101/2022.02.17.480574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontally Modulated Vagal Tone Inhibits Inflammatory Responses to Prevent Telomere Damage in Healthy Participants

Abstract: Background: Accumulated senescent cells are proposed to be one of the main drivers of age-related pathology through disruption of tissue structure and function. We recently proposed the Neuro-Immuno-Senescence Integrative Model (NISIM; Ask et al., 2018) which relates prefrontally modulated vagal tone and subsequent balance between vagal and sympathetic input to the spleen to inflammatory responses leading to generation of reactive oxygen species and oxidative telomere damage. The NISIM is based on converging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…It is thus hard to say how the results would have been if CRP type had been specified or if IL-6 had been assessed instead. It is worth mentioning that in the preliminary analyses reported in the preprint for the present study ( Ask and Sütterlin, 2022 , preprint), an association was found between vmHRV and CRP when including participants with vmHRV outside the normal range.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is thus hard to say how the results would have been if CRP type had been specified or if IL-6 had been assessed instead. It is worth mentioning that in the preliminary analyses reported in the preprint for the present study ( Ask and Sütterlin, 2022 , preprint), an association was found between vmHRV and CRP when including participants with vmHRV outside the normal range.…”
Section: Discussionmentioning
confidence: 56%
“…We would particularly like to thank Leiv Arne Rosseland for help with organizing the study, Christian Tronstad for analysis of IBIs and quantification of HRV indices, and Naomi Azulay for help with detecting outliers in the HRV data. A preprint of this manuscript is available at bioRxiv ( Ask and Sütterlin, 2022 , preprint).…”
mentioning
confidence: 99%
“…Not only did HRV indices not (cross-sectionally) mediate this association, but they were, for the most part, also not significantly correlated with childhood maltreatment or LTL. This was surprising given the majority of the literature, as limited as it is, has shown lower resting cardiac vagal control in individuals having experienced childhood maltreatment (29–36) as well as those with shorter TL (50,52–55). However, the existing literature has examined the relation between childhood maltreatment or LTL with HRV primarily in younger individuals, often with a focus on female participants, whereas our study included a sex proportional sample of older individuals suffering from chronic disease.…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have examined the associations between HRV and TL with shorter TL consistently associated with lower resting (HRV) cardiac vagal control (50,(52)(53)(54)(55). However, contradictory results have emerged in the three studies that have examined stress reactivity.…”
mentioning
confidence: 99%